Kegagalan Intelijen dalam Memahami Lingkungan Strategis: Analisis Penarikan Pasukan Amerika Serikat dari Afghanistan 2021 - Hanisyah Claudya Hermanto; Kaila Aura Mevalia; Aulia Zahrannissa Yunash; Muhammad Fazal Aidin; Rama Gala Dewa; Izma Shabry Pratama; Ivandra Solihin (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to analyze the failure of United States intelligence to understand Afghanistan’s strategic environment, which led to the collapse of the Afghan government after the withdrawal of US troops in 2021. This incident is a significant example in intelligence studies because it demonstrates the disparity between predictions made by the intelligence community and the reality on the ground. This study uses a qualitative descriptive approach, utilizing the Intelligence Failure Theory proposed by Richard K. Betts and the strategic environment concept developed by Colin S. Gray as the basis for analysis. The results show that the intelligence failure was not caused by limited information but by weaknesses in the analysis and interpretation of the developing conditions in Afghanistan. The United States intelligence community tended to focus on quantitative military aspects such as personnel numbers, combat capabilities, and weaponry strength. Meanwhile, qualitative strategic factors such as low morale in Afghan security forces, weakened government legitimacy, high levels of corruption, and the increasing influence of the Taliban in various regions did not receive adequate attention in strategic assessments. This study also found that cognitive biases and political considerations in the decision-making process also influenced the utilization of intelligence findings. This condition resulted in various available warnings being unable to be translated into effective policies to anticipate changing situations. The research findings confirm that intelligence success is largely determined by the ability to comprehensively understand the strategic environment through the integration of quantitative and qualitative information, resulting in more accurate assessments and supporting effective national security decision-making.